Prohibitin participates in the HIRA complex to promote cell metastasis in breast cancer cell lines - Xiaoqing Huang; Jinji Liu; Qinghui Ma (FEBS Open Bio, 2020)
Prohibitin (PHB) is a highly conserved, ubiquitously expressed, multifunctional protein with a well‐characterized function as a chaperone‐stabilizing mitochondrial proteins. Recently it was reported that nuclear PHB participates in HIRA chaperone complexes and regulates downstream gene expression via cell cycle independent deposition of H3.3 into DNA. However, the role of PHB in cancer progression remains controversial with conflicting reports in the literature, perhaps due to its cell type‐dependent subcellular localization. Here, we report that the increased expression of nuclear PHB is positively correlated with metastasis of breast cancer cell lines. We showed PHB participates in the HIRA complex by interacting with HIRA through the linker region of the PHB domain and stabilizes all components of the HIRA complex in breast cancer. Overexpression of nuclear PHB resulted in a higher enrichment of histone H3.3 deposited by the HIRA complex at the promoters of mesenchymal markers. This coincided with an increased gene expression level of these markers, and induced EMT in breast cancer. Overall, these molecular and structural mechanisms suggest that nuclear PHB could hold promise as a potential target for cancer therapy.